Mission in Secularised Contexts of Europe : Contemporary Narratives and Experiences - Jorgensen, Knud, 1942-; Biehl, Michael, 1956-; Behera, Marina Ngursangzeli (Book collections on Project MUSE., 2020)
"This volume deals with religion and church today, in light of the secularized contexts in Europe. It challenges the church to let its imagination be captured by the directions in which Western European societies are headed, and to rethink its mission accordingly. New situations everywhere demand careful study. The book prompts the church to retell and recast the meaning of the gospel in different contexts for the present age, and offers a sensitive, nuanced exploration of this new frontier for Christian mission. At one and the same time, contextually informed, richly textured, and theologically profound."--Publisher.